Prevalence of pollen‐induced allergic rhinitis with high pollen exposure in grasslands of northern China. Issue 6 (23rd March 2018) - Wang, X.‐Y.; Ma, T.‐T.; Wang, X.‐Y.; Zhuang, Y.; Wang, X.‐D.; Ning, H.‐Y.; Shi, H.‐Y.; Yu, R.‐L.; Yan, D.; Huang, H.‐D.; Bai, Y.‐F.; Shan, G.‐L.; et al.
Abstract: Background: The aim of this study was to investigate the prevalence of epidemiologic and physician‐diagnosed pollen‐induced AR (PiAR) in the grasslands of northern China and to study the impact of the intensity and time of pollen exposure on PiAR prevalence. Methods: A multistage, clustered and proportionately stratified random sampling with a field interviewer‐administered survey study was performed together with skin prick tests (SPT) and measurements of the daily pollen count. Results: A total of 6043 subjects completed the study, with a proportion of 32.4% epidemiologic AR and 18.5% PiAR. The prevalence was higher in males than females (19.6% vs 17.4%, P  =   .024), but no difference between the two major residential and ethnic groups (Han and Mongolian) was observed. Subjects from urban areas showed higher prevalence of PiAR than rural areas (23.1% vs 14.0%, P  <   .001). Most PiAR patients were sensitized to two or more pollens (79.4%) with artemisia, chenopodium, and humulus scandens being the most common pollen types, which were similarly found as the top three sensitizing pollen allergens by SPT. There were significant regional differences in the prevalence of epidemiologic AR (from 18.6% to 52.9%) and PiAR (from 10.5% to 31.4%) among the six areas investigated. PiAR symptoms were positively associated with pollen counts, temperature, and precipitation ( P  <   .05), but negatively with wind speed and pressure P  <   .05). Conclusion: Pollen‐induced AR (PiAR) prevalence in the investigated region is extremely high due to high seasonal pollen exposure, which was influenced by local environmental and climate conditions.